Mining clinical pathways for daily insulin therapy of diabetic children - Deja, Rafał; Froelich, Wojciech; Deja, Grażyna (Zielona Góra: Uniwersytet Zielonogórski)
We propose a decision support framework (DSF) assisting insulin therapy of diabetic children. Our DSF relies on a medical treatment graph (MTG), which models and graphically represents clinical pathways. Using the MTG, it is possible to plan and adapt medical decisions dependent upon the current health state of a patient and the progress of the treatment. Our MTG fits well with the requirements of clinical practice. The presented work is a cooperative effort of researchers in computer science and medicine. The MTG model has been thoroughly tested and validated using real-world clinical data. The usefulness of the approach has been confirmed by physicians.
Keywords: decision support systems; modeling clinical pathways; diabetes mellitus